Role of camping in the treatment of childhood obesity - Di Pietro, M.; Campanaro, P.; D'Angelo, et al., G. (Acta Biomedica Atenei Parmensis, 2004)
Obesity is constantly increasing among children. Since treatment for obesity on outpatient bases often fails, we evaluated whether camps may help to improve eating habits. Forty-one children, 21 males and 20 females (BMI > 97° percentile, weight excess > 30%,Tanner stage I) agreed to participate to a 8 day camp. After 1-year follow-up, measurements carried out by plicometry, bioelectrical impedance,metabolic and hormonal evaluations, showed a significant reduction of skinfolds, as well as glycemic and insulinemic response to the oral glucose tolerance test. These results suggest that camps may help to improve nutritional and physical education and psychological outcome of obese children.